Feasibility of an Integrated Treatment Approach for Youth with Depression, Suicide Attempts, and Substance Use Problems. Issue 2 (3rd April 2021) - Goldston, David B.; Curry, John F.; Wells, Karen C.; Kaminer, Yifrah; Daniel, Stephanie S.; Esposito-Smythers, Christianne; Doyle, Otima; Sapyta, Jeffrey; Tunno, Angela M.; Heilbron, Nicole; Roley-Roberts, Michelle
ABSTRACT: Depression, suicidal behaviors and substance use problems frequently co-occur, and treatment for youth with these co-occurring problems is often fragmented and challenging. An integrated cognitive-behavioral treatment approach that builds upon a relapse prevention framework and applies common core skills, language, and approach for treating these related problems may be clinically beneficial. Following a description of the integrated approach, we present results of a pilot trial (n = 13) to examine the acceptability and feasibility of the Cognitive-Behavioral Therapy – Relapse Prevention (CBT-RP) intervention plus enhanced treatment as usual (TAU) compared to enhanced TAU alone. The feasibility of the CBT-RP + TAU intervention was reflected by high rates of retention (86%). The acceptability was reflected in positive evaluations regarding the helpfulness of the intervention by adolescents and families. The majority of youth in both CBT-RP + TAU and TAU alone groups evidenced reductions in depression and suicide ideation from study entry to Week 20. Patterns of reduction were more consistent, however, for youth receiving CBT-RP + TAU, and reductions were slower to emerge for some youth receiving TAU alone. Reductions in alcohol and marijuana problems were similar, but half of the youth in TAU alone (and none in the CBT-RP + TAU group) had emergency department visits related to psychiatric crises or substance-related problems. These findings, although based on a small sample, underscore the feasibility and acceptability of an integrated cognitive-behavioral relapse prevention approach for youth with depression, suicide attempt histories, and substance use problems.